Vindicar y reivindicar - Rogel Vide, Carlos; Alcolado Chico, Mª Teresa; De Lamo Merlini, Olga (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
Given that the Spanish word reivindicación 1 (L. vindicatio rei, reivindicatio) has originally been a species of the genus vindicación 2 (L. vindicatio), this article aims at critically analysing the generic value currently assigned to it by considering the appropriateness of its different meanings as shown in the Spanish Academy’s Dictionary (Diccionario de la Real Academia Española), in particular the inclusion of the meaning to recover in the essence of the word, and the applicability of reivindicar 3 (L. vindicare rei) in the sense of simply claiming on the basis of quasi-ownership or other unspecified titles. To that effect, this article considers vindicatio under Roman law and reivindicación under Spanish historic law and in the different editions of the Royal Academy’s Dictionary. Finally some odifications are eventually suggested to various entries in the Dictionary.
Keywords: To Recover; To claim or recover; To claim or demand; To recover